Keragaman Bakteri Selulolitik Rumen Sapi Bali Dengan Teknik Biomolekuler - Muhammad Jufri; Nurjannah Nurjannah; Fadillah Salabilah; Nurwahidah Nurwahidah (Universitas Pahlawan Tuanku Tambusai, 2024)
The Balinese cow are able to utilize low quality feed to meet basic the needs The reserch aims to study the diversity of rumen bacteria of Balinese cow that is maintained in the people’s farm of Somba Opu District of Gowa Regency. The subjects of this research consisted of 8 adult Balinese cow that were obtained from the people’s farm of Somba Opu District of Gowa Regency. Adult Balinese cow was divided into two groups, i.e. control group consisting of 3 cows and treatment group consisting of 5 cows. The former was given local feeds of straw and field grass and the latter was given the same feed plus suplement feed. The results of the research indicate that nutritional content in the feed for control group consists of crude protein (22.81%) and crude fiber (4.41%), while the one in treatment group consistens of crude protein (7.47%) and crude fiber (35.19%). This indicates that nutritional content of the treatment group is higher than that of control group. The high nutrition in the feed of treatmnet group is indicatede by high protein and low fiber. This is caused by the use of urea, fish meal, and soybean meal. The high fiber in the feed is caused by feed materials consisting of straw and field grass. Thus, the result indicates that nutritional content in the treatment group is higher than the one in control group and the pH value of fluid rumen is affected by the content of VFA, NH3, and lactic acid.